The use of the moss, Calymperes Delessertii besch., as a bioindicator to airborne heavy metals - Low, K. S.; Lee, C. K.; Loi, S.T.; Phoon, Azhar (Universiti Pertanian Malaysia, 1985)
A detailed study on the accumulation of aerial heavy metals by the moss, Calymperes delessertii Besch. was conducted. Heavy metals studied were Zn, Cd, Ni, Fe, Mn, Pb and Cu. The suitability of the moss as a bioindicatoT to these aerial metals was also discussed.